2021
DOI: 10.1093/toxres/tfab017
|View full text |Cite
|
Sign up to set email alerts
|

Protection of apigenin against acrylonitrile-induced sperm and testis injury in rats: involvement of activation of ASK1-JNK/p38 signaling pathway

Abstract: This study aims to clarify if apigenin (AP) could play a pivotal role in attenuating acrylonitrile (ACN)-induced sperm and testis injury by inhibiting ASK1-JNK/p38 signaling pathway. Male Sprague–Dawley rats were randomly divided into five groups: a control group (corn oil), an ACN group (ACN 46 mg kg−1), an ACN + AP1 group (ACN + AP 117 mg kg−1), an ACN + AP2 group (ACN + AP 234 mg kg−1) and an ACN + AP3 group (ACN + AP 351 mg kg−1). The ACN + AP groups were given ACN by gavage after a pretreatment with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that ROS are agonists of MAPK family members [ 12 , 13 ]. Upstreams of JNK are at least two classes of kinases, MAPKKKs (ASK1) and MAPKKs (MKK4, MKK7), which sequentially phosphorylate and activate JNK through a cascade of reactions [ 14 , 15 ]. Zhu et al have demonstrated that tanshinone exerts its cerebral protective effects by scavenging reactive oxygen species (ROS) and inhibiting inflammatory responses during cerebral ischemia-reperfusion injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ROS are agonists of MAPK family members [ 12 , 13 ]. Upstreams of JNK are at least two classes of kinases, MAPKKKs (ASK1) and MAPKKs (MKK4, MKK7), which sequentially phosphorylate and activate JNK through a cascade of reactions [ 14 , 15 ]. Zhu et al have demonstrated that tanshinone exerts its cerebral protective effects by scavenging reactive oxygen species (ROS) and inhibiting inflammatory responses during cerebral ischemia-reperfusion injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 100 µmol/L dose provided the most protection against apoptosis-induced DNA damage and loss of motility/function. Apigenin may inhibit sperm apoptosis and necrosis, by regulating the balance between pro-apoptotic and anti-apoptotic factors, such as caspases, Bcl-2, and Bax 31 , 34 , 35 . Shi, et al 35 , investigated the protective effects of apigenin against acrylonitrile-induced sperm and testis injury in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin may inhibit sperm apoptosis and necrosis, by regulating the balance between pro-apoptotic and anti-apoptotic factors, such as caspases, Bcl-2, and Bax 31 , 34 , 35 . Shi, et al 35 , investigated the protective effects of apigenin against acrylonitrile-induced sperm and testis injury in rats. The results suggested that apigenin treatment significantly improved sperm quality and reduced testicular injury in rats exposed to acrylonitrile.…”
Section: Discussionmentioning
confidence: 99%
“…1,3-Butadiene may be linked to ovarian atrophy, testicular atrophy, and male infertility [ 39 ]. Acrylonitrile, cyanide, vinyl chloride, and ethylene oxide were also recognized as being potentially toxic for reproduction [ 40 , 41 , 42 , 43 , 44 , 45 ]. These studies provided part of the support for our findings.…”
Section: Discussionmentioning
confidence: 99%